2017
DOI: 10.1634/theoncologist.2016-0319
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Strategies to Prevent Cisplatin-Induced Nephrotoxicity

Abstract: Hydration is essential for all patients to prevent cisplatin-induced nephrotoxicity. Specifically, short-duration, low-volume, outpatient hydration with magnesium supplementation and mannitol forced diuresis (in select patients) represent best practice principles for the safe use of cisplatin. 2017;22:609-619 IMPLICATIONS FOR PRACTICE: The findings contained within this systematic review show that (a) hydration is essential for all patients to prevent cisplatin-induced nephrotoxicity, (b) short-duration, low-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(212 citation statements)
references
References 39 publications
5
207
0
Order By: Relevance
“…Thus, it is essential to attenuate the acute manifestations and renal failure along with subclinical reduced kidney function. A recent systematic review was conducted to examine the efficacy of hydration therapy in the prevention or amelioration of CIN (9). However, the findings of the reviewed studies showed that hydration therapy was useful only in patients receiving high-dose CDDP and in some patients, over-diuresis resulted in dehydration (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is essential to attenuate the acute manifestations and renal failure along with subclinical reduced kidney function. A recent systematic review was conducted to examine the efficacy of hydration therapy in the prevention or amelioration of CIN (9). However, the findings of the reviewed studies showed that hydration therapy was useful only in patients receiving high-dose CDDP and in some patients, over-diuresis resulted in dehydration (9).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review was conducted to examine the efficacy of hydration therapy in the prevention or amelioration of CIN (9). However, the findings of the reviewed studies showed that hydration therapy was useful only in patients receiving high-dose CDDP and in some patients, over-diuresis resulted in dehydration (9). Thus, currently, no ideal nephroprotective agent exists in clinical use for CIN treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not included in the GLIM criteria, the evaluation of fluid accumulation is included in the AND and ASPEN diagnostic characteristics, and the evaluation of fluid accumulation is an important aspect of nutrition assessment . Supportive intravenous fluids administered as part of a cancer care plan can impact weight and lead to variability in weights . The hydration status of cancer patients can vary based on oral fluid intake and fluid losses, and the influence of this should be considered as part of the weight loss evaluation.…”
Section: Oncology Patient Populationmentioning
confidence: 99%
“…Numerous hydration schedules exist. A recent systematic review by Crona et al recommends hydration schedules with a short‐duration, a low hydration volume, and magnesium and potassium supplementation.…”
Section: What Is Known and Objectivementioning
confidence: 99%